The Impact of Teacher Training, School Leadership, and Curriculum Innovation on Student Performance and Teacher Job Satisfaction in Secondary Schools - Hanum, Gilang Kartika (The Eastasouth Journal of Learning and Educations, 2024)
This study investigates the impact of teacher training, school leadership, and curriculum innovation on student performance and teacher job satisfaction in secondary schools. Using a quantitative research design, data were collected from 200 secondary school teachers through a structured questionnaire, and analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that teacher training, school leadership, and curriculum innovation each have significant positive effects on both student performance and teacher job satisfaction, with school leadership demonstrating the strongest influence. These results highlight the importance of comprehensive professional development, supportive leadership, and relevant curriculum updates in enhancing educational outcomes. The study offers valuable insights for policymakers, school administrators, and educators, emphasizing the need for integrated strategies that foster a productive and engaging learning environment.